Understanding the triacylglycerol-based carbon anabolic differentiation in Cyperus esculentus and Cyperus rotundus developing tubers via transcriptomic and metabolomic approaches - Honglin Zhang; Zhitao Zhu; Yining Di; Jixun Luo; Xianyue Su; Yong Shen; Qing Liu; Tao Liu; Xiaoyu Xu (BMC Plant Biology)
Abstract Background Yellow nutsedge (Cyperus esculentus, known as ‘YouShaDou’ in China, YSD) and purple nutsedge (Cyperus rotundus, known as ‘XiangFuZi’ in China, XFZ), closely related Cyperaceae species, exhibit significant differences in triacylglycerol (TAG) accumulation within their tubers, a key factor in carbon flux repartitioning that highly impact the total lipid, carbohydrate and protein metabolisms. Previous studies have attempted to elucidate the carbon anabolic discrepancies between these two species, however, a lack of comprehensive genome-wide annotation has hindered a detailed understanding of the underlying molecular mechanisms. Results This study utilizes transcriptomic analyses, supported by a comprehensive YSD reference genome, and metabolomic profiling to uncover the mechanisms underlying the major carbon perturbations between the developing tubers of YSD and XFZ germplasms harvested in Yunnan province, China, where the plant biodiveristy is renowned worldwide and may contain more genetic variations relative to their counterparts in other places. Our findings indicate distinct expression patterns of key regulatory genes involved in TAG biosynthesis and lipid droplet formation, including transcriptional factors and structural genes such as ABI3 transcriptional factor, rate-limiting enzymes GPAT3/6/9 and DGAT2/3, and oleosin and caleosin homologs. Furthermore, our omics data suggest that these differences in gene expression are not the sole contributors to the diverse tuber compositions. Instead, complex interactions among highly regulated catalytic reactions, governing carbohydrate, protein, and species-specific metabolite metabolisms, such as starch and sucrose metabolic pathways, flavonoid and amino acids biosynthetic pathways, collectively contribute to the pronounced carbon anabolic differentiation primarily evident in TAG accumulation, as well as the starch properties in mature tubers. Conclusion This study offers new metabolic insights into the high-value underground non-photosynthetic tissues of Cyperaceae species, which harbors not only high biomass productivity but also abundant nutrients as favorable food or industrial sources in the modern agriculture. The detailed omics analyses aim to deepen our understanding of the Cyperaceae species, which may potentially broaden their application values and facilitate the molecular breeding of better varieties to ameliorate the food safety problem.